Effect of Comorbidity on Outcomes of Patients with Advanced Non-Small Cell Lung Cancer Undergoing Anti-PD1 Immunotherapy - Zeng, Xianghua (Med Sci Monit, 2020)
BACKGROUND: Comorbidities are reportedly related to the survival of patients with non-small cell lung cancer (NSCLC). The purpose of this study was to explore the impact of comorbidity, assessed by the Charlson comorbidity index (CCI) and the simplified comorbidity scores (SCS) on clinical outcomes of patients with NSCLC treated with immune checkpoint inhibitors. MATERIAL/METHODS: Sixty-six patients with NSCLC who received programmed cell death protein 1 (PD1) inhibitors in our institution in the past 2 years were enrolled in this retrospective study. Data on comorbidity (CCI and SCS) and clinical outcomes, including progression-free survival (PFS), immunotherapy responses, and immunotherapy-related adverse events, were analyzed. RESULTS: The disease control rate was obviously higher among patients in the CCI <1 group than the CCI ≥1 group (P<0.001), but were similar between the SCS <8 group and SCS ≥8 group (P=0.585). The median PFS in the CCI <1 group was 271.0 days (95% CI: 214.3–327.7 days) compared with 232.0 days (95% CI: 66.2–397.8 days) for the CCI ≥1 group (P=0.0084). However, the median PFS showed no difference between the groups with SCS <8 at 271.0 days (95% CI: 138.7–403.3 days) versus SCS ≥8 at 222.0 days (95% CI: 196.2–247.8 days), P=0.2106). The incidence of adverse events was similar among patients with high versus low comorbidity indexes (CCI: 35.8% versus 23.6%, P=0.286, respectively; and SCS: 28.0% versus 29.3%, respectively, P=0.912). CONCLUSIONS: The comorbidity burden might be a predictor for survival in patients with NSCLC undergoing PD1 inhibitor immunotherapy.